Identification of a queen primer pheromone in higher termites - Klára Dolejšová; Jan Křivánek; Jitka Štáfková; Natan Horáček; Jana Havlíčková; Virginie Roy; Blanka Kalinová; Amit Roy; Pavlína Kyjaková; Robert Hanus (Communications Biology, 2022)
Abstract It is long established that queens of social insects, including termites, maintain their reproductive dominance with queen primer pheromones (QPPs). Yet, the QPP chemistry has only been elucidated in a single species of lower termites. By contrast, the most diversified termite family Termitidae (higher termites), comprising over 70% of termite species, has so far resisted all attempts at QPP identification. Here, we show that the queen- and egg-specific sesquiterpene (3R,6E)-nerolidol acts as the QPP in the higher termite Embiratermes neotenicus. This species has a polygynous breeding system, in which the primary queen is replaced by multiple neotenic queens of parthenogenetic origin. We demonstrate that (3R,6E)-nerolidol suppresses the development of these parthenogenetic queens and thus mimics the presence of mature queen(s). It acts as an airborne signal and may be used to optimize the number of queens, thus being the key regulatory element in the special breeding system of E. neotenicus.